Inovasi Agroteknologi untuk Meningkatkan Produktivitas dan Keberlanjutan Pertanian di Kepulauan Nias - Tafonao, Fedilina; Halawa, Nelceria; Telaumbanua, Enjelita; Laoli, Novita Sari; Lase, Natalia Kristiani (Jurnal Ilmu Pertanian dan Perikanan, 2024)
This research aims to explore the application of agrotechnology innovations in improving agricultural productivity and sustainability in Nias Islands. The main challenges of the agricultural sector in this region include limited resources, climate instability and minimal access to technology. The research used a mixed approach (qualitative and quantitative) with surveys, in-depth interviews and field observations. Results show that micro-irrigation technology and waste-based organic fertilizer are the most widely adopted innovations. These technologies can increase crop productivity by up to 30%, although there are still obstacles in the adoption of advanced technologies such as satellite image-based land mapping due to limited infrastructure and farmer knowledge. The research also identified positive socio-economic impacts, including improved farmer welfare and land sustainability. In conclusion, the development of simple technologies such as micro-irrigation and organic fertilizer offers great potential to improve production efficiency, provided there is close collaboration between the government, academia and local communities. Key recommendations include improved access to technology, intensive training, and integration of local wisdom in sustainability strategies.